Contents of e-Government for Pursuing Value in Indonesian Local Government - Alfira Sofia; Jann Hidajat Tjakraatmadja; Sudarso Kader Wiryono; Suhardi Suhardi (Institute of Advanced Engineering and Science, 2014)
This research aimed to explore contents of Indonesian e-Government in order to obtain expected value effectively by considering obstacles in implementing e-Government. It was achieved by reviewing basic and applied theory of e-Government development. The study entails compilation of emerged benefits by triangulation of extensive literature review, case study (by best practices city/municipality in Indonesia) and FGD. Some problems in implementing e-Government explored in this research can be solved through simple and creative ways. It found that contents exploration of all relationships between 4 elements which are government, users, system, and environment, can be effective solution, which have been implemented by all successful cities/municipalities. The finding would help government policy and decision makers design and implement policies and strategies to improve e-Government services. The research is undertaken at Indonesian local government level as the first researches in Indonesian e-Government implementation by exploring best practice contents which emerged in each city/municipality.